Tales From the Chalkface: Using Narratives to Explore Agency, Resilience, and Identity of Gay Teachers - Stones, Samuel; Glazzard, Jonathan (Frontiers in Sociology, 2020)
This study researched the personal and professional experiences of four queer teachers in England. The study used the life history method to create narratives of each participant. Semi-structured interviews were used. The narratives illuminate how personal experiences of exclusion can shape teacher identities. Additionally, the accounts suggest that the repeal of Section 28 in England in 2003 did not have an immediate effect on the identities and agency of the teachers. The Equality Act (2010) and changes to the school inspection framework had a greater influence in supporting their agency, resilience and willingness to merge personal and professional identities. Existing literature is dominated by accounts which position queer teachers as victims. We were concerned that this only presents a partial insight into the experiences of queer teachers. Although the stories that we have presented illuminate negative experiences, the narratives are largely positive, in contrast with existing literature.